2020
DOI: 10.3390/pathogens9100855
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Potentializes Conventional Therapy in Experimental Leishmaniasis

Abstract: Ursolic acid (UA) is a triterpene with a broad array of pharmacological activities. In leishmaniasis, UA killed different species of parasites, and it was active in the experimental model of cutaneous and visceral leishmaniasis. Thus, the objective of this work was to study the therapeutic efficacy of the conventional drugs amphotericin B (AmB) or glucantime (Glu) combined with UA in experimental visceral and cutaneous leishmaniasis, respectively. L. (L.) infantum-infected hamsters were treated with AmB alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Although leishmanicidal action has been observed, the authors considered that the second compound originated from the chemical reaction resulting from the extraction of the ethanolic extract and not from the plant in natura. This work corroborated the leishmanicidal effects observed during traditional treatment ( Odonne et al, 2009 ; 2011b ); in addition, it showed for the first time the production and accumulation of such classes of secondary metabolites in P. spicatus and supported further preclinical works with molecule 3 in the context of cutaneous and visceral leishmaniasis ( Jesus et al, 2020 ; de Jesus et al, 2021 ), which in fact reinforces the occurrence of important bioactive molecules in plants traditionally used to treat leishmaniasis.…”
Section: Plants Recommended For the Treatment Of Leishmaniasis By Traditional Communities Worldwidesupporting
confidence: 82%
“…Although leishmanicidal action has been observed, the authors considered that the second compound originated from the chemical reaction resulting from the extraction of the ethanolic extract and not from the plant in natura. This work corroborated the leishmanicidal effects observed during traditional treatment ( Odonne et al, 2009 ; 2011b ); in addition, it showed for the first time the production and accumulation of such classes of secondary metabolites in P. spicatus and supported further preclinical works with molecule 3 in the context of cutaneous and visceral leishmaniasis ( Jesus et al, 2020 ; de Jesus et al, 2021 ), which in fact reinforces the occurrence of important bioactive molecules in plants traditionally used to treat leishmaniasis.…”
Section: Plants Recommended For the Treatment Of Leishmaniasis By Traditional Communities Worldwidesupporting
confidence: 82%
“…Previous studies already discussed the in vitro and in vivo activities of both Lu and UA [ 26 , 37 , 69 ]; however, this is the first comparative work showing the leishmanicidal activity of related pentacyclic triterpenes in association with their structures, as well as morphological and physiological changes that took place in L. ( L. ) infantum . In addition, this is the first work showing the comparative therapeutic activity of both Lu and UA in the experimental model of chronic visceral leishmaniasis that is the most suitable model of natural infection.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that this triterpene has multispecies activity and the Brazilian strain of L. (L.) infantum may be more susceptible than the European species. Although maslinic acid exhibited absent or reduced cytotoxic activity on peritoneal macrophages from golden hamsters, an experimental model able to mimic natural infection [ 18 ], a previous study showed that this triterpene had a significant cytotoxic activity towards J774 macrophage [ 30 ], that is a tumor cell lineage, and thus the differences in the cytotoxicity data may be associated with the cell type employed. Taken together, our data suggest that maslinic acid could be considered an important molecule to develop new prototypes for the treatment of leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, golden hamsters with visceral leishmaniasis and BALB/c mice with cutaneous leishmaniasis showed a significant reduction in tissue parasitism during the treatment with this triterpene [ 16 , 17 ], and such activity was reported to be linked with the immunomodulatory activity [ 7 , 17 ]. Additionally, in experimental therapeutic approaches using combinatorial therapy, it was shown that ursolic acid potentialized the activity of glucantime in cutaneous leishmaniasis [ 18 ]. Although plenty of studies have shown the bioactivity of ursolic acid against leishmaniasis, few studies were performed to evaluate the antileishmanial activity of other related pentacyclic triterpenes, produced and accumulated by H. canum , as is the case of maslinic acid.…”
Section: Introductionmentioning
confidence: 99%